FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH PADA KOTA BATAM - Novia Sinaga; Erni Yanti Natalia (Jurnal Riset Akuntansi, 2025)
This research aims to determine the influence of the implementation of Government Accounting Standards (SAP), Human Resources (HR) competence, and the Government Internal Control System (SPIP) on the quality of the financial statements of the Batam City Regional Government. The method used in this study is a quantitative approach with a survey method used to collect data distributed to 72 respondents involved in the preparation of financial statements at the Batam City Regional Government BPKAD. The data analysis technique uses multiple linear regression with the help of SPSS30 software, including classical assumption test, partial hypothesis test, and simultaneous test. The results of the study indicate that the implementation of SAP has a significant positive effect of 0.016≤ 0.05 on the quality of financial statements. HR competence showed a significant positive influence of 0.037≤ 0.05 on the quality of financial statements, as well as SPIP had a significant positive effect of 0.008≤ 0.05 on the quality of financial statements.